Peningkatan Aktivitas dan Hasil Belajar Fisika Melalui Model Pembelajaran SETS (Science Environment Technology and Society) - Sarjono Sarjono (Universitas PGRI Semarang, 2020)
Abstract: The objective of this research is to test the effectiveness of Jigsaw learning model for increase activeness and learning outcomes. The research sample was MAN Pemalang Class X MIA semester 1 students in 2019/2020. Tthe problem formulation of the research is how the learning process was, how much the students’ physical activity and the result of learning physics through the models Science Environment Technology and Society (SETS). The results showed there was an increase in the average value of daily tests from 65,17 to 80,75 and the classical completeness from 46.88% to 87,50%, accompanied by the increase of the student’s activity. Keywords: activities and Science Environment Technology and Society (SETS).